Association between vigorous physical activity and life satisfaction in adolescents - Bin Feng; Ke Xu; Panpan Zhou (Frontiers Media S.A., 2022)
PurposeThe association between overall physical activity (PA) and life satisfaction has been confirmed in adolescents. However, the associations between different forms of PA at various intensities and life satisfaction are under-studied. This study aimed to explore the association between vigorous PA (VPA) and life satisfaction, and whether the associations vary by gender and age.MethodsUsing data from the Health Behavior in School-aged Children (HSBC) investigation, the research samples of 11- to 15-year-old adolescents were included for further. The information on VPA was collected via two self-reported questions, including frequency per week and hours per week. Life satisfaction was assessed by a ladder of 0-10 scores, with being higher indicating better life satisfaction. Logistic models were carried out to analyse the association between VPA and life satisfaction among adolescents, and results were presented with odd ratio (OR) and associated 95% confidence interval.ResultsAmong the 214,080 (49.2% male) adolescents studied, both boy and girl participants reporting higher frequency of VPA per week were more likely to be associated with higher life satisfaction (e.g., in boys, VPA for every day: OR = 1.054; in girls: VPA for every day: OR = 1.047). More hours of VPA was also associated with better life satisfaction in adolescents (in overall sample, 7 h or more: OR = 1.178).ConclusionsIn conclusion, this research provided evidence on the roles of VPA on life satisfaction among adolescents aged 11-15. Considering life satisfaction is regarded as an indicator of adolescents' psychological health development, our study supports and extends the evidence for the importance of VPA in adolescence.